Readiness of Pharmacists Based in Utah About Pain Management and Opioid Dispensing - Meghan M Balough; Stephen Nwankpa; Elizabeth J Unni (MDPI AG, 2019)
Prescription opioid use disorder is a growing epidemic and pharmacists as the dispensers of prescription drugs can play a crucial role in the management of the opioid crisis. However, few studies have examined pharmacists’ perceptions of their role in it. The objective of this study was to evaluate the perceptions of pharmacists in Utah regarding their role in the opioid epidemic. The study utilized a cross sectional online survey design to understand the pharmacist knowledge and beliefs regarding pain management, opioids, naloxone, and the various opioid risk identification tools. Frequencies, t-tests, and chi-squared were used to describe and analyze the data. A total of 239 surveys were qualified for analysis. Analysis showed that pharmacists have positive attitudes towards opioid crisis management; however, this positive attitude was higher among newer pharmacists. Though the pharmacists were knowledgeable with the opioid pharmacotherapy and prescribing guidelines, they demonstrated education needs for hands-on training when faced with a situation of prescription opioid use disorder in their practice. The use of risk identification tools was not prevalent. Results show lack of active participation by pharmacists in this major public health challenge, and the need for education in several aspects of opioid dispensing, naloxone use, and efficient use of risk identification tools.